THE ROLE OF THE MULTINATIONAL JOINT TASK FORCE IN COUNTER INSURGENCY IN NORTH EASTERN NIGERIA: THE BOKO- HARAMINSURGENCY - ODO CHRISTOPHER UBA (International Studies Journal)
This study examines the role of the Multinational Joint Task Force (MNJTF) in counter insurgency in northern eastern Nigeria. The research uses both primary and secondary sources of data from various experts and stakeholders in Borno, Yobe, Bauchi, Adamawa, Taraba, Gombe in the North Eastern Nigeria and Nigeria Institute for Policy and Strategic Studies Kuru near Jos Data was generated through questionnaires, interviews and Focus Group Discussions which were later analysed using descriptive method and thematic and content analysis of the secondary data. System theory was adopted and the genesis of insurgency in North Western Nigeria was traced. The study revealed that the counter insurgency against Boko Haram to some extent is succeeding as many of the insurgents have been killed, some repented while others fled and some surrenders their arms and themselves to the Multinational Joint Task Force. Although issues of mutual antagonistic distrust, corruption, inadequate modern equipment, lack of cooperation, poor commitments, weak coordination and poor funding among Multinational Joint Task Force member states undermined inability of Multinational Joint Task Force to end the counter insurgency in North Eastern Nigeria. The study recommends that good moral, values, religious education will serve as panaceas in controlling and bringing to an end religious insurgencies in the north eastern Nigeria and its environs.